Pengaruh Pemberian Rumput Lapangan dengan Daun Petai Cina (Leucaena leucocephala) bagi Ternak Domba - A Kamaruddin (Buletin Ilmu Makanan Ternak, 1986)
Leucaene leucocephala has been promoted to be used as a high protein forage for ruminant. This experiment was conducted to evaluate the use of leucaena as grass substitute in sheep. Five rams were used in a 5x5 Latin square experiment from october 2 to December 18, 1982. The substitution, on dry matter basis, were A=0%, B=25%, C=50%, D=75%, and E=100%. Dry matter consumption was reduced (P/0.05) by the substitutions (A=0.361 vs BCDE=0.223 kg/d). Since the leucaena was previously wilted, the substitution increased (P/0.05) water consumption (AB=0.100 vs CDE=0.195 L/d). Digestibility of dry matter (DM), crude protein (CP), and crude fiber (CF) of the 25% substitution were the best (DM : B= 62.3 vs ACDE=51.2%; CP: B=64.0 vs ACDE=55.4%;CF:B=57.1 vs ACDE=45.4%). The 25% substitution was also the best in promoting growth (B=71.4 vs ACDE=12.9 g/d) as well as the efficiency of dry matter utilization for growth (B=0.225 vs 0.0594 g gain DM).